Effects of Fiber Type and Shape on the Shear Behavior of Reinforced Concrete Corbels without Hoop Re-bars - Saleh, Ihab S.; Faleh, Saddam Kh.; Mahdi, Muthana Sh. (Salehan Institute of Higher Education, 2022)
In this research, the structural behavior of reinforced concrete brackets cast with concrete containing different types of fibers was studied. Seven samples of reinforced concrete corbels were cast and tested. One specimen was cast without fiber as a reference, and the other samples were made with six different types of fibers at a constant volume fraction (1% of the total concrete volume). The fibers used in the research were made of two different materials: steel and polyolefin. One specimen was cast with polyolefin fiber, and in the five remaining samples, steel fiber was used. Straight, crimped, and three different dimensions of hooked fiber were used. The results showed that the corbels with straight and hooked end steel fiber (6, 5, and 3 cm length), crimped steel fiber sized 3 cm, straight steel fiber sized 12 mm, and straight polyolefin fiber sizedÂ 6 cm showed 69.2%, 57.7%, 38.5%, 61.5%, 92.3%, and 100% higher cracking loads than the control corbel made with normal concrete, respectively, as well as exhibiting (51.7%, 48.3%, 31.0%, 24.1%, 12.1%, and 3.4%) higher ultimate loads than the control corbel. From these results, it can be concluded that the shape of the steel fiber clearly affects the ultimate load. For the same length, and despite the lack of aspect ratio, steel fibers gave an increase in the maximum load of 46.6% when compared with polyolefin fibers.Â Doi: 10.28991/CEJ-2022-08-03-08 Full Text: PDF